Physical activity levels in physiotherapy bachelor students - Alves Lopes, António (2020)
Background: Physical activity is one of the best ways to promote health. University students are exposed to a series of obstacles to the practice of physical activity. Health professionals, more than prescribing physical exercise, and in particular physiotherapists, should be examples of healthy lifestyles and exercise practice, it is therefore important to have an estimate of the level of activity physical activity in students, in order to identify means of promoting it in Physiotherapy students. Objective: Describe the level of physical activity of students enrolled in the Physiotherapy Bachelor degree at the Escola Superior de Saúde do Alcoitão (ESSA) in the 4 years of the course. Methods: During 2018 the level of physical activity of 99 students was evaluated, using the short version of the International Questionnaire of Physical Activity (IPAQ), distributed to the students of the 4 years of the Physiotherapy Bachelor degree using an online survey. Results: In relation to the number of days of physical activity (59.8%) of the students answered that they practice physical activity every day of the week and only (4.1%) of the individuals answered that they do not practice any day, being that in men the level of moderate activity predominates, whereas in women there is a dispersion through the three levels of activity. The first year is what reveals a higher percentage in the activity level low (46.2%) and lower in the high activity level (38.5%) compared with other school years. Discussion: Based on the results obtained in this study, health professionals should note that the transition to higher education is a critical time to promote physical activity and implement new programs of physical activity mainly among women and in the first year of the course where to be observed a lower level of physical activity. Conclusion: In addition to having skills, for the prescription and monitoring of physical exercise, physiotherapists should be an example of a healthy lifestyle and regular practice of physical activity.